A nationwide cohort study on treatment and survival in patients with malignant peripheral nerve sheath tumours. (January 2020) - Martin, Enrico; Coert, J. Henk; Flucke, Uta E.; Slooff, Willem-Bart M.; Ho, Vincent K.Y.; van der Graaf, Winette T.; van Dalen, Thijs; van de Sande, Michiel A.J.; van Houdt, Winan J.; Grünhagen, Dirk J.; Verhoef, Cornelis
Abstract: Background: Despite curative intents of treatment in localized malignant peripheral nerve sheath tumours (MPNSTs), prognosis remains poor. This study investigated survival and prognostic factors for overall survival in non-retroperitoneal and retroperitoneal MPNSTs in the Netherlands. Methods: Data were obtained from the Netherlands Cancer Registry and the Dutch Pathology Database. All primary MPNSTs were collected. Paediatric cases (age ≤18 years) and synchronous metastases were excluded from analyses. Separate Cox proportional hazard models were made for retroperitoneal and non-retroperitoneal MPNSTs. Results: A total of 629 localized adult MPNSTs (35 retroperitoneal cases, 5.5%) were included for analysis. In surgically resected patients (88.1%), radiotherapy and chemotherapy were administered in 44.2% and 6.7%, respectively. In retroperitoneal cases, significantly less radiotherapy and more chemotherapy were applied. In non-retroperitoneal MPNSTs, older age (60+), presence of NF1, size >5 cm, and deep-seated tumours were independently associated with worse survival. In retroperitoneal MPNSTs, male sex and age of 60+ years were independently associated with worse survival. Survival of R1 and that of R0 resections were similar for any location, whereas R2 resections were associated with worse outcomes. Radiotherapy and chemotherapy administrations were not associated with survival. Conclusion: In localized MPNSTs, risk stratification for survival can be done using several patient- and tumour-specific characteristics. Resectability is the most important predictor for survival in MPNSTs. No difference is present between R1 and R0 resections in both retroperitoneal and non-retroperitoneal MPNSTs. The added value of radiotherapy and chemotherapy is unclear. Highlights: Resectability is the most prognostic factor for survival in localized MPNSTs. In MPNSTs, NF1, older age, tumour size, and depth are associated with poorer survival. Retroperitoneal MPNST is a small subgroup with a worse prognosis. R0 and R1 resections have similar survival in MPNSTs of any location. The added value of radiotherapy and chemotherapy is unclear for survival in MPNSTs.